Media Exposure to COVID-19 Predicted Acute Stress: A Moderated Mediation Model of Intolerance of Uncertainty and Perceived Social Support - He, Xiangcai; Zhang, Yu; Chen, Meng; Zhang, Jihong; Zou, Weixing; Luo, Yu (Frontiers in Psychiatry, 2021)
Background: Previous studies have found that disaster-related media exposure could predict acute stress responses. However, few studies have investigated the relationship between media exposure to COVID-19 and acute stress, and less is known about the mechanisms that translate media exposure to COVID-19 into acute stress. The current study explored the impact of media exposure to COVID-19 on acute stress, and examined the mediating role of intolerance of uncertainty (IU) and the moderating role of perceived social support (PSS). Methods: A total of 1483 Chinese participants (Mage = 27.93 years, SD = 8.45) completed anonymous online questionnaires regarding media exposure to COVID-19, IU, PSS, and acute stress during the COVID-19 outbreak in China. Results: Media exposure to COVID-19 was positively related to acute stress, and IU partially mediated this relationship. The direct effect of media exposure to COVID-19 on acute stress, and the relationship between IU and acute stress, were both moderated by PSS. The impacts of both media exposure to COVID-19 and IU on acute stress were stronger for individuals with low PSS. Limitations: This study collected data in a shorter timeframe, and no assessments occurred during the follow-up, which may prevent us from detecting the changes of the relationships between variables over time. Meanwhile, the self-report method limited the validity of the data due to subjective reporting bias. Conclusions: These findings contribute to a better understanding of how and when pandemic-related media exposure affects acute stress, and provide new perspectives for the prevention to reduce psychological problems following traumatic events.